2004
DOI: 10.1111/j.1432-2277.2004.tb00517.x
|View full text |Cite
|
Sign up to set email alerts
|

Arterialisation of the portal vein as a model for the induction of hepatic fibrosis: description of microsurgical models in the rat

Abstract: Within the framework of liver transplantation, arterialisation of the portal vein in the case of non-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 42 publications
(20 reference statements)
0
1
0
Order By: Relevance
“…It is reported that PVA with unrestricted inflow induces hepatic fibrosis [25]. To investigate whether the fibrosis and ductular reaction found in the PPVA + BDI group were caused by PV hypertension or anastomosis occlusion, the patency of the anastomosis, blood inflow, and PV pressure were examined.…”
Section: Resultsmentioning
confidence: 99%
“…It is reported that PVA with unrestricted inflow induces hepatic fibrosis [25]. To investigate whether the fibrosis and ductular reaction found in the PPVA + BDI group were caused by PV hypertension or anastomosis occlusion, the patency of the anastomosis, blood inflow, and PV pressure were examined.…”
Section: Resultsmentioning
confidence: 99%